Water and air resistance of filling mixtures and the influence of aggressive media on their durability - Rakhimov Shavkat Turdimurotovich; Gaziev Uchqun Abdullayevich; Eshbayeva Farida Rismatovna (International Journal on Orange Technologies, 2020)
The article presents studies of water resistance and air resistance of filling mixtures based on industrial waste and the effect of aggressive media on their durability. The influence of the quantity and quality of copper-smelting slag and fly ash on the resistance of filling mixtures in various aggressive environments has been investigated. It has been established that the use of copper-smelting slag, with a low content of harmful impurities, makes it possible to obtain a slag-cement binder that is more resistant to aggressive media.